RISIKO PENGENDALIAN SISTEM PENGELUARAN KAS PADA BANK TABUNGAN PENSIUNAN NASIONAL PURNA BAKTI - Napitupulu, Yan Richo; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out how the internal control system of cash expenses, how to determine the misstatement of cash expenses material, and how the outcome internal control system and the misstatement cash expenses material to the fluctuation the internal control risk cash expenses at PT. BTPN Purna Bakti. The responsibility the auditor is on the opinion the financial statement wheather it is reasonable or not which has been published and wheather the financial statement has met with financial accounting standard in Indonesia.The cash flow statement which ends in 31 st December 2010,2011,2012,2013,2014, data from the financial statement which presented online on official website of Bank Tabungan Pensiunan Nasional. The data research has been carried out by using qualitative.This case the tolerance maximum error is the number which has been determined the material misstatements. In case the amount misstatement cash is â¤ from the determined amount, if it is not corrected, it will have an impact on the opinion the auditor, so the opinion of the auditor will be unqualified. Nevertheless, if there is a misstatement in cash â¥ from the determined amount and not corrected, therefore the opinion of the auditor is qualified.Keywords: control risk, material misstatement, materiality percentage, the opinion of the auditor